PEMANFAATAN NEMATODA TANAH GAMBUT TROPIS BAGI PENGEMBANGAN BIOLOGI DAN PENDIDIKAN BIOLOGI DI INDONESIA - Abdul Gafur (Bioscientiae, 2008)
Indonesia is the richest country in tropical peat lands. Increased population and, in turn,increased basic needs, has led to the use and conversion of peat lands. The success andsustainability of the exploitation requires sufficient knowledge of the properties, includingbiological, of the peat soils. Among key components in soil ecosystem, nematodes have beendemonstrated useful indicator of soil condition. However, few studies have been performed ontheir usefulness in tropical peat soils. In addition to the development of biology and thecontribution of biology to development, being a group with high density in species as well asecological diversity, nematodes provide good possibilities to be useful in biology education,particularly as local contents in peat-land-rich areas. Uniqueness of tropical peat landecosystems requires that certain factors and constraints be considered in the use of nematodes oftropical peat soils in the development of biology and biology education in Indonesia.